Evaluating the Performance of Wheat Germplasm under Drought Using Morphological and Physiological Traits - Nawaz, Hussan; Khan, Jahangir; Malghani, Zafar Ullah; Ahmed, Syed Riaz; Reki, Abdul Razzaq; Khetran, Munir Ahmed; Sadiq, Nadeem; Khan, Nanak; Rasool, Ghulam; Irshad, Muhammad Nauman; Ali, Basit (Indus Journal of Bioscience Research, 2025)
This study assessed the morphological and physiological responses of multiple genotypes under drought stress to identify key traits associated with drought tolerance and yield stability. A field experiment was conducted under controlled drought conditions, and data for 16 traits, including plant height, spikelet number, tiller count, grain yield, relative water content (RWC), chlorophyll content indices (NDVI), canopy temperature (CT), and harvest index (HI) were recorded. Analysis of variance (ANOVA) revealed significant genetic variation among genotypes for most traits. Mean comparisons with two standard checks, AZRI-96 and Local White (LW), identified superior lines such as BARDC-WW-5, BARDC-WW-9, and BARDC-WW-18, which exhibited enhanced grain yield, relative water content, and physiological resilience under drought stress. Pearson correlation analysis showed strong positive associations between RWC, NDVI, grain yield, and total dry matter, while canopy temperature was negatively correlated with these traits, indicating its potential as a stress indicator. Principal Component Analysis (PCA) reduced data dimensionality, with the first two components explaining 42.7% of variation and highlighting clusters of yield-related and physiological traits. The grouping of grain yield, harvest index, RWC, and total dry matter emphasizes their critical role in drought tolerance. These findings provide valuable insights into trait interactions under drought stress and offer reliable markers for breeding drought-resilient cultivars with improved productivity in water-limited environments.